## DLS 2 years ago DE

1. DLS

$xcosy+ycosx=\tan^{-1}x^{2}$

2. DLS

this is how i did it

3. DLS

$\frac{d(xcosy)}{dx} + \frac{d(ycosx)}{dx} = d(\tan^{-1} x^{2})$

4. DLS

$cosy-xsin \frac{dy}{dx} + \dfrac{(ycosx)}{dx} - ysinx=\frac{1}{1+x^{4}}$

5. DLS

$\frac{dy}{dx}(cosx-xsiny)=\frac{1}{1+x^{4}}-cosy+ysinx$

6. DLS

$\frac{dy}{dx}=\frac{1}{1+x^{4}(cosy-xsiny}) - \frac{cosy+ysinx}{cosx-xsiny}$

7. DLS

2nd equation is wrong sorry

8. hartnn

$$\large \frac{dy}{dx}=\frac{1}{(1+x^{4})(cosy-xsiny)}- \frac{cosy-ysinx}{cosx-xsiny}$$

9. DLS

$cosy-xsiny \frac{dy}{dx} +cosx \frac{dy}{dx}-ysinx=\frac{1}{1+x^{4}}$

10. DLS

oh so mine is correct? :O

11. hartnn

what u wrote now is correct.

12. DLS

finalans is correct right

13. hartnn

u get this $$\large \frac{dy}{dx}=\frac{1}{(1+x^{4})(cosy-xsiny)}- \frac{cosy-ysinx}{cosx-xsiny}$$

14. hartnn

cos y - y sin x

15. DLS

i got that only

16. hartnn

u got cos y+ y sin x

17. DLS

ah minor mistakes :p

18. DLS

if u open ur bracket u wud still get -cosy+ysinx i guess